The perfect me: cosmetic surgery and the social body in Egypt - S. Muñoz, María (AUC Knowledge Fountain, 2013)
There is an increasing scholarly interest around the popularization of cosmetic surgery in modern society. The medical discipline of plastic surgery is located at the crossroads of a significant number of scholarship disciplines including gender, media, consumer culture, ethics, the body, medical practices and psychology, among others. Hence, a multidisciplinary study is needed to approach the core subject of this research. However, as I find it materially impossible to address all these subtopics in this dissertation, three main sets of literature will inform my project. I will draw on feminist analysis and critique of cosmetic surgery, scholarly on social and cultural theory and studies on consumer culture and the body. I believe that these three categories are deeply interconnected with each other and the comprehensive study of them will help me explore the specific case study of the cosmetic surgery industry in Cairo. To support my theoretical framework I conducted ethnographic research, based on qualitative methodologies. For this project, I conducted semi-structured interviews with a sample of nineteen Cairene women and eighteen Egyptian surgeons. In order to avoid possible legal problems regarding privacy, the interviewed patients were not related to surgeons in any form, thus securing anonymity of those interviewed. In my case, being married to an Egyptian doctor has facilitated the access to many plastic sugeons. Their valuable testimonies over the past months have provided me with a close insight into the motivational forces that prompted patients to undergo plastic surgery. Egypt is certainly a unique case study. Current rampant social inequalities, the huge gaps between different economic levels, the Ã¢â‚¬Å“WesternizationÃ¢â‚¬Â of the social elite, the controversial position of women in society, the escalating role of the media and the Internet and the height of the Islamist influence are some of the elements that make cosmetic surgery a subject worthy of study.